Faulting process and coseismic stress change during the 30 January, 1973, Colima, Mexico interplate earthquake (Mw=7.6) - L. Quintanar; T. Mikumo; M. A. Santoyo (Geofísica Internacional, 2006)
A large thrust earthquake (Mw=7.6) occurred on January 30, 1973, on the plate interface between the subducting Cocos plate and the continental North America plate, near the triple junction between the North America, Cocos and Rivera Plates. This event might be related to two sequences of subsequent large earthquakes that occurred around this region. Although several authors have analyzed the focal mechanism and depth of this earthquake, we analyzed its source characteristics and performed a linear kinematic waveform inversion for the slip distribution over the fault plane. We find a shallow thrust mechanism (St=285°, Dip=16°, Ra=85°) consistent with the tectonic environment, with a depth of 16 km and a total moment release of 2.98x1027 dyn-cm. The results show a slip distribution with two main patches, with a maximum dislocation of 199 cm and 173 cm respectively. We calculated the coseismic stress change on and around the fault plane. This earthquake ruptured two main asperities, one downdip and southwest and the other updip and northwest of the hypocenter, with stress change of –31 and -40 bars respectively The surrounding zone of stress increase could have influenced the subsequent seismicity to a distance of up to 120 km from the hypocenter.